The effort reward imbalance model and work related stress in 3-5 Star hotels in Zimbabwe - Manyamba, Vimbiso; Ngezi, Tendayi (Africa Journals, 2021)
The issue of work related stress is a global problem that is affecting the hospitality industry. This study sought to test the applicability of the effort reward imbalance model as a measure of work related stress in 3 to 5 Star Hotels in Zimbabwe. Quantitative methods and a descriptive questionnaire survey design were employed on a random sample of 233 respondents from four purposively selected 3-5 star hotels. The study yielded 195 usable responses. Data was analysed using SPSS version 20 and Amos 20. From the results of the study it emerged that the ERI model was a fairly good fit for the Zimbabwean hotel employee population. The exploratory factor analysis yielded a four factor solution and confirmatory factor analysis a clear factorial structure similar to the original structure, though factor loadings were less significant. Goodness of fit indices showed there was a fairly good fit of the ERI model. The study concluded that the ERI model was applicable to Zimbabwean hotel employees. Recommendations included remodelling the ERI model by removing certain scale items to ensure the model is a better fit.